2006
DOI: 10.1002/nme.1825
|View full text |Cite
|
Sign up to set email alerts
|

An uncoupled directional damage model for fibred biological soft tissues. Formulation and computational aspects

Abstract: SUMMARYIn this paper we present a fully three-dimensional finite-strain damage model for fibrous soft tissue. Continuum damage mechanics is used to describe the softening behaviour of soft tissues under large deformation. The structural model is formulated using the concept of internal variables that provides a very general description of materials involving irreversible effects. We considered the internal variables associated to damage to correspond to separated contributions of the matrix and fibres. In orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
143
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 134 publications
(143 citation statements)
references
References 38 publications
0
143
0
Order By: Relevance
“…The alterations in mechanical and failure properties were assessed via uniaxial tension testing. A constitutive model composed of the Gasser-Ogden-Holzapfel model, for elastic response, and a continuum damage model, for the failure, was also employed to provide a further basis for comparison [1,2]. For the concentrations used here it was found that: collagenase treated samples showed decreased fracture stress in the axial direction only; elastase treated samples showed increased fracture stress in the circumferential direction only; and glutaraldehyde samples showed no change in either direction.…”
Section: Introductionmentioning
confidence: 99%
“…The alterations in mechanical and failure properties were assessed via uniaxial tension testing. A constitutive model composed of the Gasser-Ogden-Holzapfel model, for elastic response, and a continuum damage model, for the failure, was also employed to provide a further basis for comparison [1,2]. For the concentrations used here it was found that: collagenase treated samples showed decreased fracture stress in the axial direction only; elastase treated samples showed increased fracture stress in the circumferential direction only; and glutaraldehyde samples showed no change in either direction.…”
Section: Introductionmentioning
confidence: 99%
“…The adopted damage model uses the concept of internal variables, which provides a general description of materials involving irreversible effects and, therefore, must fulfill the Clausius-Planck inequality. We refer, e.g., to Holzapfel (2000) or Calvo et al (2007), where this damage formulation is adopted. In its material form and without thermal effects, it can be expressed as D = −Ψ + P :Ḟ ≥ 0 where D is the internal dissipation anḋ (•) is the material time derivative.…”
Section: Damage Modelmentioning
confidence: 99%
“…Moreover, we will restrict ourselves to damage on the anisotropic contribution of the isochoric part. We refer to Holzapfel (2000) and Calvo et al (2007) for the damage formulation of the isotropic part. Using the previous split form of the free energy, we postulate therefore…”
Section: Damage Modelmentioning
confidence: 99%
See 2 more Smart Citations